Exceptional record of submarine cave communities from the Pleistocene of Sicily (Italy). (1st August 2014) - Rosso, Antonietta; Sanfilippo, Rossana; Ruggieri, Rosario; Maniscalco, Rosanna; Vertino, Agostina
<x xml:space="preserve">Abstract</x> An Early Pleistocene benthic community, discovered inside the Rumena Cave in NW Sicily, Italy, was studied. Analysis of the community led to the recognition of several encrusting species – notably scleractinians, bryozoans, serpuloideans, cirripeds, foraminifera and brachiopods – and borings mostly referable to the ichnogenus Gastrochaenolites. All fossils detected are typical of the present‐day hard‐surface submarine cave biota, at both high taxonomic rank and species level. The biogenic crust, restricted to a few sectors of the cave but locally up to few centimetres thick, largely consist of scleractinians, mainly represented by dendrophylliids. Bryozoans and serpuloideans are also present with Hippaliosina depressa and Spiraserpula massiliensis, locally forming multi‐layered sheets and dense specimen aggregates, respectively. Basing mostly on the composition of the encrusting community and on morphological/morphometric features of some species, it has been hypothesized that at least part of the cave was blind when the crust formed, possibly at relatively shallow depth in a sheltered setting or, more probably, at higher depths, below the fair weather swell zone. Encrustations and borings on the rocky cave ceiling and on occasional speleothems broken surfaces document subsequent phases of cave submersion/colonization separated by emersion/erosion phases. The importance of the Early Pleistocene fossils of the Rumena Cave for the knowledge of submarine cave communities through time and for the understanding of sea‐level variations and the uplift of the area has been remarked.